Study on Control Scheme of Non-point Source Pollution in Heishui River Basin Based on SWAT Model - XU Lingyun (Renmin Zhujiang)
How to scientifically understand and effectively control non-point source pollution has become one of the important topics in river basin pollution prevention and control.Taking Heishui River Basin as the research area,this paper establishes the spatial database of basin underlying surface based on GIS platform,simulates the annual runoff,sediment and nutrient output in Heishui River Basin and its sub-basins through SWAT model,designs the environmental protection scheme from the perspective of the influence of land use change on non-point source pollution,and simulates the sediment and nutrient output in Heishui River Basin under different schemes,which can provide practical solutions for the control of non-point source pollution load in this basin.